Tanggung Jawab Agen Kredit Sindikasi dalam Hal Debitur Wanprestasi - Vivi Sylvia Purborini; Mohammad Gufron; Diah Aju Wisnuwardhani (MLJ Merdeka Law Journal, 2020)
This study aims to determine the position of the agent in a syndicated loan agreement, and the agent's responsibility when the debtorexperiences an achievement. This research is a normative juridical research which is a procedure to find the truth based on scientific logic from the normative side. The approach in this research is legislation and conceptual approach. The results showed that the agent's relationship with the creditors was the power relationship with the power of attorney. If a dispute arises between the agent and the parties in the syndicated loan agreement, the settlement is based on the provision of power of attorney in the syndicated credit document. The responsibility of the agent is divided into two, namely the agent who also participates in the syndication participant, and the agent outside the syndicated loan participant. Agents who are also creditors in syndicated loans, if debtors default, then the agent is responsible. The responsibility of the syndicated loan agent outside the syndicated loan participant is only as a liaison between the creditor and the debtor. The role of agents is limited in accordance with what is written in the agreed agreement document.DOI: https://doi.org/10.26905/mlj.v1i1.4288.